Rancang Bangun Layanan Sistem Presensi Akademik Menggunakan Qr Code pada Program Studi Ilmu Komputer Universitas Halu Oleo - Rahman, Hamka; Gunawan , Gunawan; Tenriawaru, Andi (System Information and Computer Technology (SYNCTECH), 2025)
Academic attendance is a crucial element in managing teaching and learning activities in higher education institutions. An efficiently and accurately designed attendance system contributes to optimizing student attendance records while supporting academic administrative processes. This study aims to design and develop a QR Code-based academic attendance system for the Computer Science Program at Halu Oleo University. The research employs a methodology that includes several stages: needs analysis, system design, implementation, and testing. The needs analysis phase identifies issues within the current attendance system and determines the necessary features. The system design phase involves creating the user interface, workflow, and database structure. The system is implemented using the Laravel framework, and testing is conducted to ensure the system functions according to specifications. The results of this study indicate that the designed QR Code-based attendance system operates effectively. Students can simply scan the QR Code provided by the lecturer at each class session to record their attendance. Attendance data is automatically stored in the database, which can then be accessed by lecturers and academic administration for monitoring and reporting purposes.